Developments in Language Theory 18th International Conference, DLT 2014, Ekaterinburg, Russia, August 26-29, 2014. Proceedings - Shur, Arseny M.; Volkov, Mikhail V. (Theoretical Computer Science and General Issues, 2014)
This book constitutes the proceedings of the 18th International Conference on Developments in Language Theory, DLT 2014, held in Ekaterinburg, Russia, in August 2014. The 22 full papers and 5 short papers presented together with 3 invited talks were carefully reviewed and selected from 38 submissions. The papers are organized in topical subjects on Grammars, Acceptors and Transducers for Words, Trees and Graphs, Algebraic Theories of Automata, Algorithmic, Combinatorial and Algebraic Properties of Words and Languages, Variable Length Codes, Symbolic Dynamics, Cellular Automata,  Polyominoes and Multidimensional Patterns,  Decidability Questions, Image Manipulation and Compression, Efficient Text Algorithms, Relationships to Cryptography, Concurrency, Complexity Theory and Logic,  Bio-Inspired Computing, and Quantum Computing.